2012
DOI: 10.1007/s11427-012-4407-7
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 suppresses PMA and ionomycin-induced ICAM-1 expression in endothelial cells

Abstract: Intercellular adhesion molecule-1 (ICAM-1) plays an important role in the recruitment of leukocytes to the endothelium, which causes inflammation and initiation of atherosclerosis. We have previously shown that endothelium-specific over-expression of class III deacetylase SIRT1 decreases atherosclerosis. We therefore addressed the hypothesis that SIRT1 suppresses ICAM-1 expression in the endothelial cells. Here, we found that expression of SIRT1 and ICAM-1 was significantly induced by PMA and ionomycin (PMA/Io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Sirt1 significantly decreased in human endothelial cells after hydrogen peroxide (H 2 O 2 ) exposure [39]. Sirt1 also reduced the ionomycin-induced ICAM-1 expression and attenuated the downregulation of thrombomodulin after particulate matter treatment [40], [41]. As expected, our results showed that inhibition of Sirt1 was associated with the decreased BBB permeability in our co-cultures with or without OGD exposure.…”
Section: Discussionsupporting
confidence: 81%
“…Sirt1 significantly decreased in human endothelial cells after hydrogen peroxide (H 2 O 2 ) exposure [39]. Sirt1 also reduced the ionomycin-induced ICAM-1 expression and attenuated the downregulation of thrombomodulin after particulate matter treatment [40], [41]. As expected, our results showed that inhibition of Sirt1 was associated with the decreased BBB permeability in our co-cultures with or without OGD exposure.…”
Section: Discussionsupporting
confidence: 81%
“…It was reported that Sirt1 reduces endothelial activation 42 , and overexpression of Sirt1 in ECs inhibits atherosclerosis 33 . Mechanistically, adenovirus-mediated over-expression of Sirt1 significantly inhibits PMA/Ionomycin-induced ICAM-1 expression in human umbilical vein ECs, whereas knockdown of Sirt1 by RNA interference (RNAi) results in increased expression of ICAM-1 and increases NF-κB p65 binding ability to the ICAM-1 promoter by ChIP assays in HUVECs 43 . However, the issue of whether caspase-1 in aortic ECs senses hyperlipidemia to initiate vascular inflammation via inhibiting Sirt1 was not examined until this report.…”
Section: Discussionmentioning
confidence: 99%
“…We found that SIRT1 inhibited PMA/Io-induced NF-κB [33] and NFAT transcriptional activity. Moreover, inhibition of COX-2 expression by SIRT1 in PMA/Io-treated HUVECs was largely abrogated by inhibiting NFAT or NF-κB activation.…”
Section: Discussionmentioning
confidence: 75%